2011
DOI: 10.3389/fnhum.2011.00013
|View full text |Cite
|
Sign up to set email alerts
|

Language Mapping in Multilingual Patients: Electrocorticography and Cortical Stimulation During Naming

Abstract: Multilingual patients pose a unique challenge when planning epilepsy surgery near language cortex because the cortical representations of each language may be distinct. These distinctions may not be evident with routine electrocortical stimulation mapping (ESM). Electrocorticography (ECoG) has recently been used to detect task-related spectral perturbations associated with functional brain activation. We hypothesized that using broadband high gamma augmentation (HGA, 60–150 Hz) as an index of cortical activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 93 publications
2
54
0
Order By: Relevance
“…We computed the time-frequency energy distribution of ictal activity in all recorded channels using a matching pursuit (MP) algorithm (Mallat and Zhang, 1993), which has been previously successfully used for detection of epileptic activity (Jouny et al, 2007a; Jouny et al, 2003), as well as functional activity (Boatman-Reich et al, 2010; Cervenka et al, 2011a; Cervenka et al, 2013a; Cervenka et al, 2013b; Cervenka et al, 2011b). MP is an iterative procedure that decomposes signal x(t) into a linear combination of members of a specified set of functions.…”
Section: Methodsmentioning
confidence: 99%
“…We computed the time-frequency energy distribution of ictal activity in all recorded channels using a matching pursuit (MP) algorithm (Mallat and Zhang, 1993), which has been previously successfully used for detection of epileptic activity (Jouny et al, 2007a; Jouny et al, 2003), as well as functional activity (Boatman-Reich et al, 2010; Cervenka et al, 2011a; Cervenka et al, 2013a; Cervenka et al, 2013b; Cervenka et al, 2011b). MP is an iterative procedure that decomposes signal x(t) into a linear combination of members of a specified set of functions.…”
Section: Methodsmentioning
confidence: 99%
“…29,30 It has long been recognized that cortical stimulation can affect function at a distance, 7 and that ESM does not always predict postoperative language outcomes. 10,26,31 This concern is perhaps best illustrated in somatosensory and motor cortices, where the effects of lesions are more predictable. Although stimulation of postcentral gyrus often elicits motor responses, resection of this gyrus causes sensory impairments and apraxia, but not weakness per se.…”
Section: Region Of Interest (Roi) Analysis For Each Patient We Per-mentioning
confidence: 99%
“…Although some studies have indicated poor sensitivity and specificity of ECoG mapping in relation to ESM (e.g., specificity of 78% and sensitivity of 38% during visual object naming 12 ), recent reports have suggested that in some instances it can be more predictive of postoperative language impairments than ESM. 10,26,27 More work will be required to correlate surgical outcomes with the location of resected and preserved sites identified by ESM and STFM.…”
Section: Region Of Interest (Roi) Analysis For Each Patient We Per-mentioning
confidence: 99%
“…To date, studies of the clinical utility of ECoG for preoperative functional mapping have been promising [82], but clinical decisions about surgical resections continue to rely on ESM. More studies are needed to assess the relative abilities of ECoG and ESM to predict postresection neurological impairments.…”
Section: Clinical Utility Of Functional Brain Mapping With Ecogmentioning
confidence: 99%